2013
DOI: 10.1177/0300060513488516
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of 102 cases of solid pseudopapillary neoplasm of the pancreas in China

Abstract: Surgical resection is the primary therapy for SPN, and results in a good prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The limitation of our study is the relatively small number of examined cases, especially in comparison with recent large series from Asia [7,19,32,38,47].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The limitation of our study is the relatively small number of examined cases, especially in comparison with recent large series from Asia [7,19,32,38,47].…”
Section: Discussionmentioning
confidence: 88%
“…We noted a single clinically aggressive SPN in the present series (5.9%). The percentage of cases with malignant features varies between studies, from less than 4% to more than 20% [5,19,33,35,38,49,53,85]. This may be related to differences in criteria of malignancy, follow-up protocols, adjuvant treatment, as well as patients' characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, cellular atypia, infiltration of pancreatic parenchyma and surrounding tissues, peripancreatic vascular invasion, and peripheral nerve infiltration are highly invasive pathological manifestations of SPN, and a number of studies have found that SPN has calcifications on imaging, lesions greater than 5 cm, incomplete tumor capsule, microvascular invasion, preoperative metastasis, non-radical resection, and high proliferation index. It may be a high risk factor for recurrence, but there is still no consistent conclusion on the risk factors related to postoperative recurrence and poor prognosis, and there is no evidence that postoperative adjuvant chemotherapy has a positive impact on the prognosis of SPN [ [30] , [31] , 32 ]. Because the clinical cases of invasive SPN are very rare, it is difficult to summarize and clarify the natural course of invasive SPN in clinical situations, which makes it difficult for clinicians or surgeons to provide patients and their families with information about invasive pancreatic SPN [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthily, the majority of SPNPs have been described as benign in nature; nonetheless, 10-15% of SPNPs exhibit malignant behavior and metastases ( 18 ). Surgery remains the current preferred treatment option for SPNP ( 2 4 , 6 , 19 ), and the surgical approach largely depends on the location, size, and nature of the tumor. Commonly employed surgical procedures include distal pancreatectomy, central pancreatectomy, total pancreatectomy, pancreaticoduodenectomy, etc.…”
Section: Discussionmentioning
confidence: 99%